Luteolin impacts deoxyribonucleic acid repair by modulating the mitogen-activated protein kinase pathway in colorectal cancer. Issue 4 (1st April 2022) - Song, Yelin; Yu, Jie; Li, LingLing; Wang, Lei; Dong, Liangle; Xi, Guangmin; Lu, Yun Jing; Li, Zuowei
ABSTRACT: This study aimed to investigate the effects of luteolin on colorectal cancer (CRC) and explore its underlying mechanism. HCT-116 and HT-29 cells were treated with luteolin, cisplatin, or selumetinib. The cell survival, cell proliferation, apoptosis and cell cycle distribution, and DNA damage were detected using Cell Counting Kit-8, colony formation, flow cytometry, and immunofluorescence staining analysis, respectively. Western blotting was used to detect the expression of apoptosis-related, cycle-related, DNA-damage-related, and mitogen-activated protein kinase (MAPK) pathway-related proteins. Luteolin showed inhibitory effects on cellular growth by reducing cell survival and proliferation, inducing apoptosis and DNA damage, and arresting the cell cycle in a concentration-dependent manner in HCT-116 and HT-29 cells. Meanwhile, luteolin increased the expression of pro-apoptotic proteins, p-CHK1 (central to the induction of cell cycle arrest), and DNA excision repair protein and decreased anti-apoptotic proteins, G2-M phase-related proteins, and DNA repair proteins. The combination of cisplatin and luteolin significantly decreased cell survival and increased the apoptosis rate of HCT-116 and HT-29 cells compared with cisplatin alone. Bioinformatic analysis using the Comparative Toxicogenomics Database and STITCH and MalaCards databases showed that the MAPK pathway is involved in the pharmacology of luteolin. Furthermore, western blotting demonstrated that luteolin plays an inhibitory role by suppressing the MAPK signaling pathway in CRC, which is enhanced when combined with selumetinib. Luteolin can also prevent tumourigenesis in CRC in vivo. In conclusion, luteolin suppressed cell proliferation, blocked the cell cycle, and induced DNA damage and apoptosis progression in CRC cells by mediating the MAPK pathway GRAPHICAL ABSTRACT: uf0001